Pemetaan Penelitian Pembiayaan di Baitul Mal wat Tamwil: Studi Bibliometrik VOSviewer dan Literature Review - Fahmi, Fahmi Amru Ar-Rifa'i; Agustiawan, Muhammad Iqbal; Aulia, Keisya Valentina; Aliyana, Ama Dwi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to map the development of studies on financing in Baitul Mal Wat Tamwil through a bibliometric approach with the help of a VOSviewer and a literature review. The study covers 56 years, from 1970 to 2025, with data obtained from searches on the Open Alex website using the keywords “financing in BMT” and “financing in Baitul Mal Wat Tamwil.” The search yielded a total of 568 scientific articles. These articles were then analyzed descriptively, processed using VOSviewer software, and reviewed through a literature review to obtain a visual overview of the mapping of developments in topics and research subjects related to financing in BMT. The analysis results show that publications on the funding in Baitul Mal Wat Tamwil have increased significantly yearly, but have declined in the last three years. Furthermore, based on the visual mapping with VOSviewer, it was found that research on financing in BMT is divided into 5 clusters. Meanwhile, the literature review identified 4 main themes and 42 research topics related to financing in BMT.